Key issues and explorations in shale gas fracturing - Jianchun Guo; Qianli Lu; Youwei He (Natural Gas Industry B, 2023)
During volume fracturing of shale gas reservoirs, hydraulic fractures may readily communicate with natural fractures to propagate forward and induce the formations to slip along the fracture surfaces. The resulted inter-well frac-hit and casing deformation affect the safe and efficient operation of shale gas fracturing. In addition, unpropped fractures caused by small natural fracture width lead to deteriorating fracture conductivity, which in turn impacts the stimulation effect of shale gas reservoirs. This paper discusses the three key issues, i.e. inter-well frac-hit, casing deformation and unpropped microfractures, that impact the economic exploration and exploitation of shale gas, and proposes engineering prevention and control measures through literature review and research on mechanism by integrating theoretical and experimental analysis, which have been applied on site. Firstly, after clarifying the mechanism and main controlling factors of inter-well frac-hit, an evaluation model and prediction method of frac-hit based on machine learning were established. The measures for preventing and controlling inter-well frac-hit, including temporary plugging at fracture tip and shut-in of old wells, were determined after evaluation with the well-cluster fracture model. Secondly, an analysis model of casing deformation caused by fracture shear and slippage was established after stress analysis. According to the analysis of stress on casing intersected with fractures during fracturing, it is ascertained that increase of fluid pressure within natural fractures is the main factor that causes casing deformation. The methods for preventing casing deformation were proposed in terms of fracturing operation and well construction. Thirdly, the mechanism of micro-proppant migration was analyzed by integrating the model of particle migration and the transport experiment in large-scale plate, and the experiment confirms that micro-proppant can effectively improve the fracture conductivity. It is concluded after field application that the prevention and control measures proposed for inter-well frac-hit and casing deformation can mitigate frac-hit and casing deformation significantly, and micro-proppants are conducive to improving post-frac shale gas production. The measures provide a support for large-scale and economic development of deep shale gas.